Effect of Nano-Particles on the Performance and Emission of a Diesel Engine using Biodiesel-Diesel Blend - M., Ghafoori; B., Ghobadian; G., Najafi; M., Layeghi; A., Rashidi; R., Mamat (Universiti Malaysia Pahang, 2015)
n experimental investigation was conducted in a six - cylinder, four-stroke diesel engine to establish the effects of Multi Wall Carbon Nano Tubes (MWCNT) with the dosing levels from 2.5 to 30 ppm with the waste vegetable oil (WVO) methyl esters fuel that was produced using the transestrification process, and subsequently, the WVO methyl ester was blended with diesel fuel in the proportion of 80% of diesel and 20% biodiesel by volume (B20). The Carbon nanotubes (with nano-structure (1/3) Chiral Metal and (2/3) semiconductor zigzag particles with the length of 10 μm and diameter of 5 nm with purity rate of 95%) were blended with the biodiesel fuel .The CNTs we re blended with the biodiesel with the aid of ultrasonicator. The whole investigation was conducted in the diesel engine using the following fuels: neat diesel fuel (D100), 20% biodiesel and 80% diesel by volume (B20), as well as B20 and CNT blended fuels accordingly.The experimental results revealed a considerable enhancement in the performance parameters for the CNT blended biodiesel fuels compared to the neat biodiesel and neat diesel fuel (power increased up to 17%, torque increased 18%, bsfc decreased 38.5%). Emission parameters for the CNT blended decreased compared to neat diesel and neat biodiesel fuels (HC decreased up to 22%, CO emission decreased 14%).CNT nano-additives are considered as a propitious fuel - borne catalyst to improve the fuel properties, owing to their enhanced surface area/volume ratio, quick evaporation and shorter ignition delay characteristics that help to improve the performance parameters of engine and decrease emissions